Transcriptome and digital gene expression analysis reveal immune responses of mantle and visceral mass pearl culturing in Hyriopsis cumingii - Shen, Xiaoya; Chen, Yige; Jia, Liang; He, Wang; Chen, Xiaofeng; Chen, Yiwen; Xuan, Xingrong; Li, Jiale; Bai, Zhiyi; Li, Wenjuan (Frontiers in Marine Science, 2023)
Biomineralization is a widespread phenomenon in marine mollusks and is responsible for the production of shells and pearls. However, the regulatory mechanisms governing the adaptive immune responses in the mollusk mantle and visceral mass during mineralization remain unclear. In this work, we examined the mantle and visceral mass immune responses of Hyriopsis cumingii during pearl culture using high-throughput sequencing techniques. A mantle transcriptome database was established using transcriptome sequencing technology and reference to the major databases. Digital gene expression profiling was used to identify the differentially expressed genes of mantle and visceral mass at different insertion periods. Moreover, quantitative real-time PCR was used to verify the expression of five immune-related genes. Transcriptome sequencing results showed 257,457 unigenes were identified. Digital gene expression profiles showed 1389, 3572, 1888, and 2613 differentially expressed genes (DEGs) in the mantle and visceral mass at 5, 20, 50, and 90 d after insertion, respectively, with the highest number at 20 d and the lowest at 5 d after insertion (q < 0.05). A cluster analysis of the DEGs showed similar clustering and expression features in the mantle to the control group, and at 5, 50 and 90 d, after mantle insertion. The DEGs in the visceral mass showed similar clustering and expression features to the control group and at 5, 20 and 50 d after insertion. We also screened 22 immune-related DEGs in the mantle and visceral mass during the same pearl culture period, including serine/threonine-protein kinase NLK, C-type lectin, and galectin. The greatest number of DEGs was found 90 d after insertion. Compared with the mantle, more immune-related DEGs were down-regulated than up-regulated in the visceral mass during pearl culture, indicating that the immune regulatory mechanisms in the visceral mass and the mantle differ during pearl culture, and that the visceral mass is liable to higher infection and mortality rates. Quantitative real-time PCR results showed that the expression of five immune-related genes was consistent with DGE results. Our findings will further knowledge of the immune systems that are present in the mantle and visceral mass during pearl culture.